Blood pressure behavior during mechanical thrombectomy and drugs used for conscious sedation or general anesthesia - Oliveira,Ráissa Soraya Souza de (2021)
ABSTRACT Background: The optimal blood pressure (BP) during mechanical thrombectomy for acute ischemic stroke is currently unclear. Objective: To investigate BP behavior during mechanical thrombectomy in patients with acute ischemic stroke and its relationship with drugs used for sedation or general anesthesia. Additionally, we investigated the association between BP oscillation during mechanical thrombectomy and recanalization status, and with functional outcome at discharge. Methods: Consecutive patients treated with mechanical thrombectomy for acute ischemic stroke were evaluated in a tertiary hospital from December/2009 to December/2015. Maximum, minimum, and mean systolic and diastolic BP, and mean arterial pressures were collected during the procedure. Sedative drugs were also reviewed. Results: Fifty-three patients with a mean age of 71.9 years (60.4% men) were treated with mechanical thrombectomy. The mean reduction in systolic BP and mean arterial pressure from hospital admission to mechanical thrombectomy were respectively 42 and 36 mmHg. During the procedure, oscillations were 50.4 mmHg for systolic, and 33.2 mmHg for diastolic BP. Patients treated with neuromuscular blocking drugs had more oscillation in systolic BP from hospital admission to procedure (51.1 versus 26.2 mmHg, P=0.06). The use of cisatracurium (43.9 versus 29.6 mmHg, P=0.02) and succinylcholine (44.7 versus 29.3 mmHg, P=0.01) were associated with a significant drop in BP during the procedure. Conclusions: Significant BP oscillation occurs during mechanical thrombectomy. Drugs used for conscious sedation or general anesthesia, specifically neuromuscular blocking agents, might have an influence upon BP levels.